2022
DOI: 10.5005/jp-journals-10006-2063
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mifepristone in Preinduction Cervical Ripening in Term Pregnancy

Abstract: Objective: To study the efficacy of mifepristone in preinduction cervical ripening in term pregnancy. Study design: This is a prospective observational study, done in a tertiary care hospital. Fifty pregnant women in the study group were given oral mifepristone 200 mg for preinduction cervical ripening (second dose after 24 hours if applicable) and another 50 pregnant women who underwent expectant management were included in the expectant group. The primary objective was to assess the effect of mifepristone on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…We found that women who underwent outpatient cervical ripening with mifepristone had the same rate of Bishop score improvement as women in the inpatient group at 24 h (1 (1–2) vs. 1 (1–2), P = 0.416) and 48 h (3 (2–4) vs. 3 (1–4), P = 0.527). This Bishop score improvement was the same as or slightly lower than that reported in other studies [25] , [26] , [27] , [30] , [31] , [32] , [33] , [34] , [35] , [36] .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We found that women who underwent outpatient cervical ripening with mifepristone had the same rate of Bishop score improvement as women in the inpatient group at 24 h (1 (1–2) vs. 1 (1–2), P = 0.416) and 48 h (3 (2–4) vs. 3 (1–4), P = 0.527). This Bishop score improvement was the same as or slightly lower than that reported in other studies [25] , [26] , [27] , [30] , [31] , [32] , [33] , [34] , [35] , [36] .…”
Section: Discussionsupporting
confidence: 86%
“…In a study by Hcini et al [24] , upon the use of 600 mg of mifepristone for cervical ripening at or beyond term, only 2 of 108 (1.9 %) patients reported headache and abdominal pain, and no foetal or neonatal side effects were noted. In another study comparing the outcomes of cervical ripening with mifepristone and dinoprostone in 50 women at term pregnancies, there were no differences in neonatal outcomes, including the incidence of hypoglycaemia [35] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation